2014
DOI: 10.1099/vir.0.063461-0
|View full text |Cite
|
Sign up to set email alerts
|

Domains of the cucumber mosaic virus 2b silencing suppressor protein affecting inhibition of salicylic acid-induced resistance and priming of salicylic acid accumulation during infection

Abstract: The cucumber mosaic virus (CMV) 2b silencing suppressor protein allows the virus to overcome resistance to replication and local movement in inoculated leaves of plants treated with salicylic acid (SA), a resistance-inducing plant hormone. In Arabidopsis thaliana plants systemically infected with CMV, the 2b protein also primes the induction of SA biosynthesis during this compatible interaction. We found that CMV infection of susceptible tobacco (Nicotiana tabacum) also induced SA accumulation. Utilization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 40 publications
0
38
0
Order By: Relevance
“…Systemic infection of susceptible plants by certain compatible viruses, for example during the infection of nn genotype tobacco by TMV, does not result in increased SA biosynthesis by the host (Malamy et al ., ). However, cauliflower mosaic virus (CaMV) (Love et al ., ), cucumber mosaic virus (Zhou et al ., ), potato virus Y (Krečič‐Stres et al ., ) and turnip mosaic virus (Whitham et al ., ) induce increased SA accumulation and SA‐responsive gene expression as they spread through their susceptible hosts. SCMV infection was previously reported to cause SA accumulation in maize inbred lines (Wu et al ., ), but the role of SA in SCMV–maize interactions was not clarified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic infection of susceptible plants by certain compatible viruses, for example during the infection of nn genotype tobacco by TMV, does not result in increased SA biosynthesis by the host (Malamy et al ., ). However, cauliflower mosaic virus (CaMV) (Love et al ., ), cucumber mosaic virus (Zhou et al ., ), potato virus Y (Krečič‐Stres et al ., ) and turnip mosaic virus (Whitham et al ., ) induce increased SA accumulation and SA‐responsive gene expression as they spread through their susceptible hosts. SCMV infection was previously reported to cause SA accumulation in maize inbred lines (Wu et al ., ), but the role of SA in SCMV–maize interactions was not clarified.…”
Section: Resultsmentioning
confidence: 99%
“…SCMV infection induced endogenous SA accumulation in maize plants and increased expression of the SA‐regulated genes ZmPR1 and ZmPR5 . Increases in SA accumulation have been observed in several compatible plant–virus interactions (Krečič‐Stres et al ., ; Love et al ., ; Whitham et al ., ; Wu et al ., ; Zhou et al ., ). Results of a previous study suggested an increase in SA in maize infected by SCMV (Wu et al ., ) but the role of SA in SCMV infection remains unclear.…”
Section: Discussionmentioning
confidence: 97%
“…It was shown that CaMV P6 suppressor inhibits SA-induced gene expression through NPR1 (Laird et al, 2013;Love et al, 2012). Upon CMV but not CMVΔ2b suppressor mutant strain infection the SA levels accumulated Zhou et al, 2014). 2b was shown to have a dual action: it inhibited expression of few SA-regulated genes but in the same time enhanced the effect of SA on others.…”
Section: Connecting Antiviral Silencing To Hormone Signalingmentioning
confidence: 97%
“…Since CMV infection has been reported to induce salicylic acid signaling in this study (Fig. 4) and previously (44,68,69), one may expect that rgs-CaM autoactivates its antiviral function for SAR during CMV infection via its perception of CMV 2b. However, rgs-CaM did not effectively inhibit CMV infection in relatively young plants (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…8A). CMV 2b has been reported to interfere with salicylic acid and jasmonic acid signaling (44,68,69). Ca 2ϩ influx induced by A23187 caused rgs-CaM protein accumulation in both wild-type and 2b-expressing transgenic plants (Fig.…”
Section: Discussionmentioning
confidence: 99%